The Role of Positron Emission Tomography/Computed Tomography Imaging in Head and Neck Cancer after Radical Chemoradiotherapy: a Single Institution Experience. Issue 11 (November 2017) - Nelissen, C.; Sherriff, J.; Jones, T.; Guest, P.; Colley, S.; Sanghera, P.; Hartley, A.
Abstract: Aims: Positron emission tomography/computed tomography (PET/CT) is used to restage head and neck cancer 3 months after chemoradiotherapy. The purpose of this study was to determine the negative predictive value (NPV) of a scan reported as having no abnormal uptake and the positive predictive values (PPV) for different maximum standardised uptake value (SUVmax) thresholds. Materials and methods: Patients with squamous cell carcinoma of the oro-/hypopharynx/larynx ( n  = 206) were included. SUVmax and subsequent locoregional recurrence were documented. Results: The median SUVmax was 11.2 (range 4–33)/4.6 (range 2–30), respectively, in patients with/without definite primary site recurrence ( P  = 0.004). The median SUVmax was 4.4 (range 2.6–15.6)/3.1 (range 2.1–4.6), respectively, in patients with/without definite nodal recurrence ( P  = 0.003). The NPV for a scan reported as having no abnormal uptake was 92%. The PPV for the SUVmax thresholds 4, 6 and 8, respectively, were 53, 65 and 92% (primary site) and 93, 100 and 100% (nodes). Conclusions: The NPV of PET/CT after chemoradiation is consistent with the literature and underlines the importance of PET/CT in restaging the primary site if salvage neck dissection is considered. The overall PPV of PET/CT remains low but is high for nodal SUVmax > 4. These data could be used to design risk-stratified follow-up schedules. Highlights: NPV of PET/CT post-chemoradiotherapy in head and neck cancer is high. PPV for neck disease is 100% if SUVmax > 6 at 3 months. PPV for primary site recurrence is 92% if SUVmax > 8 at 3 months. Trend towards higher PPV in p16-negative versus p16-positive patients. Data could be used to design risk-stratified follow-up schedules.